Implementation of Symmetric Key Cryptography Algorithm Using Vigenere Cipher Method for Data Security - Nadia Widari Nasution; Okki Kurnia; Devid Trinaldo Simatupang; Syahelma Fithri (Politeknik Ganesha Medan, 2026)
Confidentiality when sending text messages is a very important aspect in today's information technology era. One of the most appropriate security methods to use is cryptography. To secure data using cryptography, encryption and decryption are required. Encryption is the process by which information/data to be transmitted is converted into a form that is almost unrecognizable as the original information using a specific algorithm. Decryption is the reverse of encryption, converting the encrypted form back into the original information. The results of this research indicate that messages can be protected more strongly and securely, so that if a message is hijacked or intercepted by an irresponsible party, the hijacker will have difficulty deciphering its contents. This ensures the confidentiality and authenticity of the message until it reaches the recipient. In this research, message encryption and decryption are done using the Python programming language.